2017
DOI: 10.1109/tim.2017.2672478
|View full text |Cite
|
Sign up to set email alerts
|

Precision Packet-Based Frequency Transfer Based on Oversampling

Abstract: Frequency synchronization of a distributed measurement system requires the transfer of an accurate frequency reference to all nodes. The use of a general-purpose, packetbased network for this aim is analyzed in the paper, where oversampling is considered as a means to counter the effects of packet delay variation on time accuracy. A comprehensive analysis, that includes the stability of the local clock, is presented and shows that frequency transfer through a packet network of this kind is feasible, with an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Other contributions propose alternative ways to perform the frequency synchronization and estimate the synchronization uncertainty. The former can be faced using oversampling method [29]. It requires a high rate exchange of timing packets reducing the available bandwidth for the applications and its timing performance can be affected in extreme conditions such as network congestion.…”
Section: White Rabbit Synchronization Protocolmentioning
confidence: 99%
“…Other contributions propose alternative ways to perform the frequency synchronization and estimate the synchronization uncertainty. The former can be faced using oversampling method [29]. It requires a high rate exchange of timing packets reducing the available bandwidth for the applications and its timing performance can be affected in extreme conditions such as network congestion.…”
Section: White Rabbit Synchronization Protocolmentioning
confidence: 99%
“…Exel et al [9] reported that the asymmetry of a link delay occurs by the different twist rates of the Ethernet cable pairs used for transmission and reception; thus, they configured links to ensure that the transmission path of the PTP packets used the same cable pairs. Giorgi et al [10] proposed software-based packet sampler with an oversampling strategy, which filters out packets with delays exceeding a certain value to reduce the possibility of asymmetry. The reliable range of packet delay is derived with the soft-min machine learning function and weight function defined by the Boltzmann distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous works partially resolve the issue or introduce their own weaknesses. They require additional hardware supports [7], [11], [18], address only specific components of the total packet delay [7]- [9], [13], [21], [22], require additional or large amounts of packet exchanges [10]- [12], [20], or do not provide high accuracy at the nanosecond level [10], [12], [13], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Exel et al [5] reported that the asymmetry of a link delay occurs by the different twist rates of the Ethernet cable pairs used for transmission and reception; thus, they configured links to ensure that the transmission path of the PTP packets used the same cable pairs. Giorgi et al [6] proposed software-based packet sampler with an oversampling strategy, which filters out packets with delays exceeding a certain value to reduce the possibility of asymmetry. The reliable range of packet delay is derived with the soft-min machine learning function and weight function defined by the Boltzmann distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous works partially resolve the issue or introduce their own weaknesses. They require additional hardware supports [3], [7], address only specific components of the total packet delay [3]- [5], [9], require additional packet exchanges [6]- [8], or do not provide high accuracy at the nanosecond level [6], [8], [9].…”
Section: Introductionmentioning
confidence: 99%